Analyzing the Relationship between Economic Indicators, Demographics, and Islamic Bank Assets in High-Asset OIC Countries - Fitri Utami (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Islamic banking has expanded substantially over the past decade, however the number of institutions does not always correspond to the scale of asset accumulation. This study aims to examine the key macroeconomic and demographic determinants that influence Islamic banking asset growth in the ten countries with the highest Islamic banking assets globally. Using panel data regression with a fixed effect model over the period 2015 to 2023, this study investigates the impact of per capita income, inflation, oil prices, and Muslim population on asset growth. The findings show that, collectively, these variables significantly affect the growth of Islamic banking assets. However, only per capita income (10% significance level) and Muslim population (1% significance level) have significant individual effects, while inflation and oil prices are statistically insignificant. The novelty of this research lies in its extended time frame (2015–2023) and its focus on asset accumulation rather than profitability, an aspect relatively underexplored in previous studies. Furthermore, by concentrating on top-performing Islamic banking countries, the study offers fresh insights into the structural and religious-demographic drivers of Islamic financial development. These findings provide practical implications for policymakers and Islamic financial institutions seeking to foster sustainable growth, particularly in regions with strategic demographic advantages. Perbankan Islam mengalami pertumbuhan signifikan dalam satu dekade terakhir, namun jumlah institusi yang ada belum mencerminkan skala akumulasi aset yang berhasil dihimpun. Penelitian ini bertujuan untuk mengkaji determinan makroekonomi dan demografis utama yang memengaruhi pertumbuhan aset perbankan Islam di sepuluh negara dengan total aset perbankan Islam tertinggi di dunia. Dengan menggunakan regresi data panel model efek tetap (fixed effect model) selama periode 2015 hingga 2023, studi ini menganalisis pengaruh pendapatan per kapita, inflasi, harga minyak, dan populasi Muslim terhadap pertumbuhan aset. Hasil analisis menunjukkan bahwa secara simultan, variabel-variabel tersebut berpengaruh signifikan terhadap pertumbuhan aset perbankan Islam. Namun secara parsial, hanya pendapatan per kapita (signifikan pada tingkat 10%) dan populasi Muslim (signifikan pada tingkat 1%) yang berpengaruh signifikan, sedangkan inflasi dan harga minyak tidak signifikan secara statistik. Kebaruan penelitian ini terletak pada cakupan waktu yang lebih panjang (2015–2023) dan fokusnya pada dimensi akumulasi aset, bukan profitabilitas, yang masih jarang dikaji dalam studi sebelumnya. Selain itu, fokus pada negara-negara dengan kinerja perbankan Islam tertinggi menghasilkan temuan baru terkait peran faktor struktural ekonomi dan demografis-religius. Temuan ini memberikan implikasi praktis bagi pembuat kebijakan dan lembaga keuangan syariah dalam merancang strategi penguatan sektor perbankan Islam jangka panjang.